EVALUASI KONDISI FISIK DOMINAN PADA ATLET DAYUNG DRAGON BOAT USM TAHUN 2018 - Aldiansyah Akbar; Junaidi (Jurnal Penjaskesrek, 2018)
Research entitled. "Evaluation of dominant physical conditions in rowing sports (a study on USM rowing athletes in 2018" raised the physical condition of one component that must be improved by each athlete. With the presence of an athlete's physical abilities greatly affect the development of achievement. In rowing physical abilities an athlete can be seen from the ability of athletes to demonstrate perfectly rowing skills throughout the race.To support physical abilities during the race an exercise program is required in a physical condition that is arranged in a planned, programmed, and carried out continuously.The dominant physical condition needs to be improved in rowing is cardiovascular endurance, endurance of arm muscles, endurance of abdominal muscles, arm strength, arm muscle power, shoulders and flexibility. Research conducted was population research, which included all individuals who became the population in this study. This subject is all USM rowing athletes in 2018 totaling 16 athletes. From the data analysis the results of lung cardiac endurance ability are at a very low category level, with an average value of 1,774. The endurance ability of the arm and shoulder muscles is at the level of the less category, with an average value of 5.75. Endurance ability of abdominal muscles is at the level of good category, with an average value of 63.1. Arm muscle strength is at an adequate category level, with an average value of 31.75. The ability of the arm and shoulder muscles to be at the level of the category is less, with an average value of 3. The ability of sit and rich is in good category with the average value of 17.75. Abstrak Penelitian yang berjudul. “evaluasi kondisi fisik dominan pada cabang olahraga dayung (suatu penelitian pada atlet dayung USM tahun 2018” ini mengangkat kondisi fisik salah satu komponen yang harus ditingkatkan oleh setiap atlet. Dengan adanya Kemampuan fisik seorang atlet sangat mempengaruhi perkembangan prestasi. Pada cabang olahraga dayung kemampuan fisik seorang atlet dapat dilihat dari kemampuan atlet memperagakan dengan sempurna keterampilan dayung sepanjang perlombaan. Untuk mendukung kemampuan fisik selama perlombaan diperlukan suatu program latihan kondisi fisik yang disusun secara terencana, terprogram, teratur dan dilaksanakan secara kontinyu. Kondisi fisik dominan perlu ditingkatkan dalam cabang olahraga dayung adalah daya tahan jantung paru, daya tahan otot lengan, daya tahan otot perut, kekuatan lengan, power otot lengan, bahu dan kelentukan. Penelitian yang dilakukan adalah penelitian populasi yaitu semua individu yang menjadi populasi dijadikan sampel dalam penelitian ini. Subjek dalam penelitian ini adalah seluruh atlet Dayung USM Tahun 2018 yang berjumlah 16 atlet. Dari analisis data diperoleh hasil kemampuan daya tahan jantung paru berada pada tingkat katagori kurang sekali, dengan nilai rata-rata 1.774. Kemampuan daya tahan otot lengan dan bahu berada pada tingkat katagori kurang, dengan nilai rata-rata 5.75. Kemampuan daya tahan otot perut berada pada tingkat katagori baik, dengan nilai rata-rata 63.1. Kemampuan kekuatan otot lengan berada pada tingkat katagori cukup, dengan nilai rata-rata 31.75. Kemampuan power otot lengan dan bahu berada pada tingkat katagori kurang, dengan nilai rata-rata 3. Kemampuan sit and rich berada pada kaegori baik dengan nila rata – rata 17.75. Kata kunci: Evaluasi, kondisi fisik dominan, olahraga dayung